Sildenafil Alleviates Bronchopulmonary Dysplasia in Neonatal Rats by Activating the Hypoxia-Inducible Factor Signaling Pathway - Park, Hyoung-Sook (Am J Respir Cell Mol Biol, 2013)
Bronchopulmonary dysplasia (BPD) is a major cause of morbidity in premature infants receiving oxygen therapy. Currently, sildenafil is being examined clinically to improve pulmonary function in patients with BPD. Based on the pharmacological action of sildenafil, the elevation of cyclic guanosine 3′,5′-monophosphate (cGMP) in lung tissue is considered to underlie its beneficial effects, but this mechanism is not understood at the molecular level. Here, we examined the possibility that sildenafil helps the pulmonary system adapt to hyperoxic stress. To induce BPD, fetal rats were exposed to LPS before delivery, and neonates were exposed to hyperoxia, followed by intraperitoneal injections of sildenafil. Alveolarization was impaired in rats exposed to hyperoxia, and alveolarization significantly recovered with sildenafil. An immunohistochemical examination revealed that sildenafil effectively increased vascular distribution in lung tissue. Furthermore, the oxygen sensor hypoxia-inducible factor (HIF)–1/2α and the angiogenic factor vascular endothelial growth factor (VEGF) were highly expressed in the lungs of sildenafil-treated rats. In human small-airway epithelial cells, HIF-1/2α and its downstream genes, including VEGF, were confirmed to be induced by sildenafil at both the protein and mRNA levels. Mechanistically, cGMP in airway cells accumulated after sildenafil treatment because of interfering phosphodiesterase Type 5, and subsequently cGMP activated HIF-mediated hypoxic signaling by stimulating the phosphoinositide 3-kinase (PI3K)–v-akt murine thymoma viral oncogene homolog 1 (AKT)–mammalian target of rapamycin (mTOR) pathway. This study provides a better understanding about the mode of action for sildenafil, and suggests that HIF can be a potential target for treating patients with BPD.